Pengaruh Diameter Nozzle dan Tebal Layer Terhadap Ketelitian Objek Printer 3D - Dicky Seprianto (Jurnal Teknik Mesin, 2021)
Rapid prototyping is closely related to 3D printers (additive manufacturing). Rapid prototyping is a technique for making a prototype model from a CAD file which is the final result, while a 3D printer is one of the processes. The 3D printer process is by melting the filament layer by layer to form a component or product. The 3D printer melting process uses a heater on the nozzle. This study aims to analyze the effect of nozzle diameter and layer thickness on the accuracy (dimensional measurement) of 3D printer objects. To determine the precision, a test object was made based on ASTM D995-08. The variation of nozzle diameter used is 0.2 mm and 0.5 mm, while the variation in layer thickness is 0.1 mm and 0.3 mm. In this study, delta type 3D printing was used with polylactic acid (PLA) material to make test objects. Dimension measurement using ASTM D5947-06. Analysis of the measurement results used ANOVA with a 2-level factorial design type and a 2 factorial interaction (2FI) model design using Design-Expert®. software. From the actual measurement results, the most accurate (precise) results are obtained on the test object with a variation of the nozzle parameters with a diameter of 0.2 mm and a layer thickness of 0.1 mm. From the analysis of the specimen measurement data, it can be concluded that the nozzle diameter significantly affects the response of length, width and height while the thickness of the layer affects the response of the length and width of the specimen.